DO INTERNATIONAL REGULATIONS FORCE TRANSPORT COMPANIES TO REDUCE THEIR CARBON EMISSIONS? - Diana-Claudia PERȚICAȘ; Roxana GAVRILUȚ; Olivia-Andreea MARCU; Adrian-Gheorghe FLOREA (Annals of the University of Oradea: Economic Science)
The pressure on conventional resources, along with the consequences of global warming, have imposed a reaction by International Economic and Environmental Organizations regarding their more careful management. Our study analyzes the current state of the vehicle park in Romania from the point of view of the degree of aging of the vehicles distributed in the development regions of Romania, analyzing the situation of almost 10,000 trucks with a mass of more than 7.5 tons. The novelty of this research is not given from the analysis of the types of vehicles that can be purchased, which is a controversial and long-debated issue in the specialized literature. The model we developed shows that in most cases the earnings from salaries and wages, and the inflation rate have a positive influence on the decision to purchase a new freight vehicle, as against the length of modernized roads and the GDP. We believe that increased attention should also be given to increasing the degree of digitization in transport companies, an activity that can highlight a series of negative consequences of old vehicles.